THE IMPORTANCE OF SENTINEL LYMPH NODE BIOPSY IN EARLY INVASIVE BREAST CANCER: EXPERIENCE OF 3. GENERAL SURGERY DEPARTMENT IN LUTFI KIRDAR KARTAL EDUCATION AND RESEARCH HOSPITAL - Mehmet Eser; Levent Kaptanoğlu; Hasan Ediz Sıkar; Hasan Fehmi Küçük; Cengiz Volkan Menteş; Fırat Tutal; Hüseyin Uzun; Necmi Kurt (European Journal of Breast Health, 2007)

(untitled)
AIM: Sentinel lymph node biopsy is a minimal invasive technique, which is an alternative for axillary dissection. In this prospective study we tried to evaluate accuracy of sentinel lymph node biopsy in early stage breast cancer, using only isosulphane blue solution.MATERIAL and METHOD: 40 patients without axillary metastasis were included in our study. Age, diagnostic biopsies, preoperative stage, time and number of sentinel lymph node biopsies, histopathological evaluations, postoperative stage, early postoperative complications were evaluated.RESULTS: Mean detection time for sentinel lymph nodes was 15 (5-25) minutes by 38 patients. Mean number for detected nodes was 1 (1-4). We found mean 16 (9-30) nodes with axillary dissections. 19 patients had axillary metastasis. Only a single patient showed negative sentinel lymph node result. By 37 patients we have shown that sentinel lymph node biopsy is a reliable method. We could not detect any recurrences or metastasis.CONCLUSION: Sentinel lymph node biopsy is a reliable method in evaluation of axillary node status. Axillary dissections can be avoided through sentinel lymph nodes without metastasis.